2003
DOI: 10.1002/chin.200403276
|View full text |Cite
|
Sign up to set email alerts
|

PARACEST Agents: Modulating MRI Contrast via Water Proton Exchange

Abstract: Theoretical chemistry Theoretical chemistry Z 0350 PARACEST Agents: Modulating MRI Contrast via Water Proton Exchange -[53 refs.]. -(ZHANG, S.; MERRITT, M.; WOESSNER, D. E.; LENKINSKI, R. E.; SHERRY, A. D.; Acc. Chem. Res. 36 (2003) 10, 783-790; Dep. Chem., Univ. Tex., Dallas, Richardson, TX 75083, USA; Eng.) -Lindner 03-276

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(135 citation statements)
references
References 1 publication
4
131
0
Order By: Relevance
“…w over 100 kHz. Because of these requirements, and the added requirement for CEST agent-bound protons to be clearly resolved from other endogenous protons in vivo, the most effective CEST agents are paramagnetic (PARACEST) agents based on water exchange off of lanthanide coordination sites (Zhang et al, 2003a;Zhang et al, 2001). PARACEST agents are complexes somewhat similar to the gadolinium-containing T 1 agents, but they incorporate "low relaxivity" lanthanides with short Tie (e.g., Eu 3+, Dy 3+, or Nd 3+) in place of Gd 3+.…”
Section: R~+ Kws 1 +(T;/te)(cn/lll)mentioning
confidence: 99%
“…w over 100 kHz. Because of these requirements, and the added requirement for CEST agent-bound protons to be clearly resolved from other endogenous protons in vivo, the most effective CEST agents are paramagnetic (PARACEST) agents based on water exchange off of lanthanide coordination sites (Zhang et al, 2003a;Zhang et al, 2001). PARACEST agents are complexes somewhat similar to the gadolinium-containing T 1 agents, but they incorporate "low relaxivity" lanthanides with short Tie (e.g., Eu 3+, Dy 3+, or Nd 3+) in place of Gd 3+.…”
Section: R~+ Kws 1 +(T;/te)(cn/lll)mentioning
confidence: 99%
“…Further, compounds, probes, or ligands that contain an NMR -visible nuclei (e.g., fl uorine -19) can be designed and used to monitor tissue distribution (Wolf et al, 1998 ). The complex chemical exchange of magnetization that occurs can also be leveraged to enable chemical exchange -sensitive techniques, such as chemical exchange saturation transfer ( CEST ) and paramagnetic CEST ( PARACEST ) (Zhang et al, 2003 ;Woods et al, 2006 ;Sherry and Woods, 2008 ).…”
Section: Discovery Of Novel Tracersmentioning
confidence: 99%
“…For example, such is the mechanism behind CEST and PARACEST contrast agents [41,65,67], where off-resonance pulses saturate out the magnetization of particular exchangeable protons within the molecular complexes comprising the CEST/PARACEST agents. Once these off-resonance protons subsequently undergo chemical exchange with the surrounding bulk water protons, the total on-resonance magnetization, and hence the signal intensity acquired from the surrounding bulk water pool, is diminished.…”
Section: Magnetization Transfer For Amplification Of the Detection Ofmentioning
confidence: 99%
“…The beauty of such off-resonant agents is that they may be selectively addressable or detectable through their different chemical shifts, allowing a form of multispectral or "color" contrast rather than the traditional "monochrome" brightening or darkening of T 1 and T 2 agents. Recently, it has been demonstrated that certain paramagnetic chelates, so called PARACEST agents, can also be used, with the paramagnetic ion leading to larger chemical shifts of the exchangeable protons, increasing the spectral bandwidth achievable [41,67]. CEST principles have recently also been applied to hyperpolarized xenon agents [68] and to lipid-based nanoparticles [40], including liposome and micelle structures that each aggregate together many CEST molecules [69] to effectively increase contrast per composite particle.…”
mentioning
confidence: 99%